Cho biểu thức: \(\left(\frac{1+2x}{4+2x}-\frac{x}{3x-6}+\frac{2x^2}{12-3x^2}\right)\cdot\frac{24-12x}{6+13x}\)
a) Tìm điều kiện xác định của biểu thức. Rút gọn biểu thức.
b) Tìm giá trị của x để giá trị của biểu thức có giá trị dương.
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1. Where do you study ? - Currently, I'm studying at Co Nhue 2 Secondary School.
2. What subject do you ? Why ?
- I to study Literature the most because they aim to educate about morality, personality and ideology through literary works rich in emotions and images.
3. How many people in your family ? Who are they ?
- My family consists of a total of four people : dad, mom, me anh my younger brother.
1,I study at cam vu primary school
2,I english best because I want to talk with foreign friends
3,there are five people in my family.It is a grandmother,father,mother,sister and me
Vì \(\overline{x216y}\)chia 2 dư 1 \(\Rightarrow y\)là số lẻ (1)
mà \(\overline{x216y}\)chia 5 dư 3 \(\Rightarrow y\in\left\{3;8\right\}\)(2)
Từ (1) và (2) \(\Rightarrow y=3\)
Ta có: \(\overline{x2163}\)chia 9 dư 5 \(\Rightarrow\overline{x2163}-5=\overline{x2158}⋮9\)
\(\Rightarrow x+2+1+5+8=16+x⋮9\)
\(\Rightarrow x=2\)
Vậy số cần tìm là \(22163\)
Ta có :
\(\overline{x216y}\)chia 2 dư 1 \(\Rightarrow y\)là 1 số lẻ ( * )
\(\overline{x216y}\)chia 5 dư 3 \(\Rightarrow y\in\left\{3;8\right\}\)( ** )
Từ ( * ) và ( ** ) \(\Rightarrow y=3\)
Ta lại có :
\(\overline{x2163}\)chia 9 dư 5 \(\Rightarrow\overline{x2163}-5=\overline{x2158}⋮9\)
\(\Rightarrow x+2+1+6+3⋮9\)
\(\Rightarrow x+16⋮9\)
\(\Rightarrow x=2\)
Vậy số cần tìm là : \(22163\)
Bài 11:
1) Sửa lại đề là: \(A=127^2+146.127+73^2\)
\(\Rightarrow A=127^2+2.127.73+73^2\)
\(\Rightarrow A=\left(127+73\right)^2\)
\(\Rightarrow A=200^2\)
\(\Rightarrow A=40000\)
Vậy \(A=40000.\)
2) Sửa lại đề là: \(B=9^8.2^8-\left(18^4-1\right).\left(18^4+1\right)\)
\(\Rightarrow B=\left(9.2\right)^8-\left[\left(18^4\right)^2-1^2\right]\)
\(\Rightarrow B=18^8-\left(18^8-1\right)\)
\(\Rightarrow B=18^8-18^8+1\)
\(\Rightarrow B=0+1\)
\(\Rightarrow B=1\)
Vậy \(B=1.\)
4) \(D=\left(3+1\right).\left(3^2+1\right).\left(3^4+1\right).\left(3^8+1\right).\left(3^{16}+1\right)\)
\(\Rightarrow2D=\left(3-1\right).\left(3+1\right).\left(3^2+1\right).\left(3^4+1\right).\left(3^8+1\right).\left(3^{16}+1\right)\)
\(=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(=\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(=\left(3^8-1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(=\left(3^{16}-1\right)\left(3^{16}+1\right)\)
\(=3^{32}-1\)
\(\Rightarrow D=\frac{3^{32}-1}{2}\)
Find the wrong sentences( Tìm các câu sai )
1. She has two sausage . > Sausages
2.How old is you? > are
3. My Mother is watching TV. > \(\varnothing\)
4.My brother and my sister is go to Ba Na Hills last week. > went
5.He has a stomach ache. > \(\varnothing\)
1, She has two sausage => Sausages
2, How old is you ? => Are
3, My mother is watching TV ( không có lỗi sai )
4, My brother and my sister is go to Ba Na Hills last week => Are
5, He has a stomach ache (Không có lỗi sai )
Học tốt ^^^
\(\left(3+\sqrt{5}\right)\left(\sqrt{10}-\sqrt{2}\right)\sqrt{3-\sqrt{5}}\)
\(=\left(3+\sqrt{5}\right).\sqrt{2}.\left(\sqrt{5}-\sqrt{1}\right).\sqrt{3-\sqrt{5}}\)
\(=\left(3+\sqrt{5}\right).\left(\sqrt{5}-1\right).\sqrt{6-2\sqrt{5}}\)
\(=\left(3+\sqrt{5}\right).\left(\sqrt{5}-1\right).\sqrt{5-2\sqrt{5}+1}\)
\(=\left(3+\sqrt{5}\right).\left(\sqrt{5}-1\right)\left(\sqrt{5}-1\right)\)
\(=\frac{6+2\sqrt{5}}{2}.\left(\sqrt{5}-1\right)^2\)
\(=\frac{\left(\sqrt{5}+1\right)^2.\left(\sqrt{5}-1\right)^2}{2}=\frac{\left[\left(\sqrt{5}-1\right)\left(\sqrt{5}+1\right)\right]^2}{2}\)
\(=\frac{\left(5-1\right)^2}{2}=\frac{4^2}{2}=8\)
a) Ta có \(\frac{x}{3}=\frac{y}{5}=\frac{x+y}{3+5}=-\frac{32}{8}=-4\)(dãy tỉ số bằng nhau)
=> x = -12 ; b = -20
b) Ta có : \(\frac{x}{y}=\frac{9}{11}\Rightarrow\frac{x}{9}=\frac{y}{11}=\frac{x+y}{9+11}=\frac{60}{20}=3\)(dãy tỉ số bằng nhau)
=> x = 27 ; y = 33
a. Áp dụng t/c của dãy tỉ số bằng nhau, ta có :
\(\frac{x}{3}=\frac{y}{5}=\frac{x+y}{3+5}=\frac{-32}{8}=-4\)
Suy ra :
+) \(\frac{x}{3}=-4\Leftrightarrow x=-12\)
+) \(\frac{y}{5}=-4\Leftrightarrow y=-20\)
b. \(\frac{x}{y}=\frac{9}{11}\Leftrightarrow\frac{x}{9}=\frac{y}{11}\)
Áp dụng t/c của dãy tỉ số bằng nhau, ta có :
\(\frac{x}{9}=\frac{y}{11}=\frac{x+y}{9+11}=\frac{60}{20}=3\)
Suy ra :
+) \(\frac{x}{9}=3\Leftrightarrow x=27\)
+) \(\frac{y}{11}=3\Leftrightarrow y=33\)
a) \(ĐKXĐ:\hept{\begin{cases}x\ne\pm2\\x\ne-\frac{13}{6}\end{cases}}\)
Đặt \(A=\left(\frac{1+2x}{4+2x}-\frac{x}{3x-6}+\frac{2x^2}{12-3x^2}\right)\cdot\frac{24-12x}{6+13x}\)
\(\Leftrightarrow A=\left(\frac{1+2x}{2\left(x+2\right)}-\frac{x}{3\left(x-2\right)}-\frac{2x^2}{3\left(x^2-4\right)}\right)\cdot\frac{12\left(2-x\right)}{6+13x}\)
\(\Leftrightarrow A=\frac{3\left(2x^2-3x-2\right)-2\left(x^2+2x\right)-4x^2}{6\left(x-2\right)\left(x+2\right)}\cdot\frac{12\left(2-x\right)}{6+13x}\)
\(\Leftrightarrow A=\frac{-2\left(6x^2-9x-6-2x^2-4x-4x^2\right)}{\left(x+2\right)\left(6+13x\right)}\)
\(\Leftrightarrow A=\frac{-2\left(-6-13x\right)}{\left(x+2\right)\left(6+13x\right)}\)
\(\Leftrightarrow A=\frac{2}{x+2}\)
b) Để biểu thức nhận giá trị dương
\(\Leftrightarrow\frac{2}{x+2}>0\)
\(\Leftrightarrow x+2>0\)
\(\Leftrightarrow x>-2\)
Vậy để biểu thức có giá trị dương thì \(x>-2\)